2013
DOI: 10.1371/journal.pone.0061174
|View full text |Cite
|
Sign up to set email alerts
|

Visual Cues Given by Humans Are Not Sufficient for Asian Elephants (Elephas maximus) to Find Hidden Food

Abstract: Recent research suggests that domesticated species – due to artificial selection by humans for specific, preferred behavioral traits – are better than wild animals at responding to visual cues given by humans about the location of hidden food. \Although this seems to be supported by studies on a range of domesticated (including dogs, goats and horses) and wild (including wolves and chimpanzees) animals, there is also evidence that exposure to humans positively influences the ability of both wild and domesticat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 52 publications
2
35
0
Order By: Relevance
“…Next, the elephants were given a "solid-lid" control condition to rule out the potential effect of the elephants perceiving nonolfactory information about the quantities of food presented (one set of 12 trials with solid lids only, 24 g of seeds vs. none). They were then trained on a small ratio (1:8, i.e., 4 vs. 32 g of seeds) to ensure that they understood that both buckets could contain food [these elephants had extensive previous experience with object-choice tasks in which only one bucket had food (34,43)]. The elephants all reached criterion (80% correct within a set of 12 trials) in eight or fewer sets (mean = 2.67 sets).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the elephants were given a "solid-lid" control condition to rule out the potential effect of the elephants perceiving nonolfactory information about the quantities of food presented (one set of 12 trials with solid lids only, 24 g of seeds vs. none). They were then trained on a small ratio (1:8, i.e., 4 vs. 32 g of seeds) to ensure that they understood that both buckets could contain food [these elephants had extensive previous experience with object-choice tasks in which only one bucket had food (34,43)]. The elephants all reached criterion (80% correct within a set of 12 trials) in eight or fewer sets (mean = 2.67 sets).…”
Section: Resultsmentioning
confidence: 99%
“…This time frame commenced as soon as the subject used his/her trunk to contact a bucket. The table was then pulled back, the cable ties were cut, and the perforated lids were replaced with solid lids positioned upside down on top of the buckets [subjects were previously trained in earlier experiments to remove the lids from the buckets when the lids were placed upside-down on top of the openings (34,43)]. The table was again extended, allowing the subject to remove the lid from one bucket to potentially retrieve the reward (the "choice phase").…”
Section: Apparatus and Materialsmentioning
confidence: 99%
“…Past research on the African elephants' visual system states that they can detect important conspecific behavioral cues, such as ear and trunk movements (Byrne et al, 2009;Kahl & Armstrong, 2000) as well as important heterospecific behavioral cues, such as human pointing, face and body orientation (Smet & Byrne, 2013; however, research by Plotnik et al (2013) found that Asian elephants could not follow human pointing cues. The results of the current study suggest that Asian elephants are able to detect more subtle visual cues, which may be important for establishing and maintaining social bonds.…”
Section: Discussionmentioning
confidence: 99%
“…Further work on problem-solving (e.g. Foerder et al, 2011;Plotnik et al, 2011Plotnik et al, , 2013Plotnik et al, , 2014Mizuno et al, 2015) coupled with multi-modal input and reward/non-reward designs could be helpful in deciphering what deterrents would be best to test in wild settings as one tool for reducing crop raiding and ameliorating human-elephant conflict.…”
Section: Elephant Sensesmentioning
confidence: 99%